Ecotechnologies for the Reconstructions of Railway Subgrade Construction - Sestakova, Janka; Miksik, Milan (Communications - Scientific letters of the University of Zilina, 2001)
Nowadays the question of the constant stability of the geometry position of the track in connection with modernization of the railway network in our territory is relevant. That is conditioned by the compliance of the rated carrying capacity of the whole subgrade construction. Therefore construction layers are built, which take part in the total increase of its quality. The building and operating work of the railway transport has to be managed with regard to the protection of the environmental rules. Observing the rules is available by the implementation of recycled materials. It’s possible to accomplish it by using the technologies, which focus on working activities directly to the center track line.